EKSISTENSI GURU DALAM CERMIN AKU - Ach. Tijani (Khatulistiwa, 2017)
Choosing to be a teacher cannot be separated from the self. Become a teacher also should be a self. However, constitution of reality precedes the identity, so the choice to become a teacher may not be of a self selecting. At this point, self as the subject come under pressure and compulsion. In response to these issues, a teacher has to get out of everything that forms itself from the outside. The possible option is the freedom of atheistic and theistic.